1993
DOI: 10.1159/000107340
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Heterogeneity in Mild Alzheimer's Disease

Abstract: In order to investigate neuropsychological differences in patients with mild AD, we carried out a pilot study on 28 patients with a clinical diagnosis of mild dementia (CDR: 0.5–1) using an extensive neuropsychological battery, in comparison with 28 normal controls. The results of a cluster analysis, applied on the neuropsychological variables, showed the existence of at least two main subgroups of patients. Cluster 1 patients had a mean age of 61.1 years and showed a greater impairment on measures of language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 22 publications
4
34
0
1
Order By: Relevance
“…Neuropathological studies have generally sought to establish orders of severi ty [68] by demonstrating variations in senile plaque [2,69] or neurofibrillary pathology [70] or loss of synapses [71][72][73][74], However, neuropathology cannot address varia tions in rate of progression. Alternatively, several studies in living patients have pointed to heterogeneity in the clinical presentation of cognitive abnormalities in AD patients [42,[75][76][77][78], The cognitive variations between patients are particularly prominent in mild stages of the illness [79], when clinical symptoms are the manifestation of disease affecting the relatively intact, complex nervous system [80] with sociocultural overlays. Further, AD may be caused by a variety of different etiological agents which can increase the potential variation of the presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological studies have generally sought to establish orders of severi ty [68] by demonstrating variations in senile plaque [2,69] or neurofibrillary pathology [70] or loss of synapses [71][72][73][74], However, neuropathology cannot address varia tions in rate of progression. Alternatively, several studies in living patients have pointed to heterogeneity in the clinical presentation of cognitive abnormalities in AD patients [42,[75][76][77][78], The cognitive variations between patients are particularly prominent in mild stages of the illness [79], when clinical symptoms are the manifestation of disease affecting the relatively intact, complex nervous system [80] with sociocultural overlays. Further, AD may be caused by a variety of different etiological agents which can increase the potential variation of the presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed by a psychologist, and was carried out as previously described [9] with the use of Mini Mental State Examination (MMSE) [10], and of tests for which Italian norms are available, allowing correction for age, gender, and education [9].…”
Section: Fig 1 A-e Clinical History Of 5 Lbd Patients (Eases 1(a) mentioning
confidence: 99%
“…Early-onset patients have greater degree of language, visuospatial or attentional disturbances [3][4][5][6][7][8][9][10], and they have a more rapid progression of cognitive deficits [9,11,12]. However, Binetti et al [13] reported a better performance on a memory task in early-than late-onset patients. The underlying pathophysiology of the onset-age effect is still uncertain, and a considerable number of researchers has assessed this issue.…”
Section: Introductionmentioning
confidence: 99%